2015
DOI: 10.3390/geosciences5030222
|View full text |Cite
|
Sign up to set email alerts
|

Petrologic and Minerochemical Trends of Acapulcoites, Winonaites and Lodranites: New Evidence from Image Analysis and EMPA Investigations

Abstract: A comprehensive classification of primitive achondrites is difficult due to the high compositional and textural variability and the low number of samples available. Besides oxygen isotopic analysis, other minerochemical and textural parameters may provide a useful tool to solve taxonomic and genetic problems related to these achondrites. The results of a detailed modal, textural and minerochemical analysis of a set of primitive achondrites are presented and compared with literature data. All the samples show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Because diffusion is particularly slow in clinopyroxene, diffusive exchange of Fe, Mg, and Ca between the pyroxenes effectively ceases at relatively high temperatures on the cooling path (particularly when cooling is rapid), at which point individual pyroxene grains effectively become closed systems. There are many reported two‐pyroxene thermometry results for type 6 ordinary chondrites in the range 950–1000 °C (see compilation in Mare et al 2014), and for primitive achondrites in the range 1000–1100 °C (Folco et al 2006; Li et al 2011; Cecchi and Caporali 2015), implying that the closure temperature of typical chondritic systems is close to the solidus temperature (cf. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because diffusion is particularly slow in clinopyroxene, diffusive exchange of Fe, Mg, and Ca between the pyroxenes effectively ceases at relatively high temperatures on the cooling path (particularly when cooling is rapid), at which point individual pyroxene grains effectively become closed systems. There are many reported two‐pyroxene thermometry results for type 6 ordinary chondrites in the range 950–1000 °C (see compilation in Mare et al 2014), and for primitive achondrites in the range 1000–1100 °C (Folco et al 2006; Li et al 2011; Cecchi and Caporali 2015), implying that the closure temperature of typical chondritic systems is close to the solidus temperature (cf. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pontlyfni does not fit with the other eight samples for any criteria (e.g., petrography, mineralogy, chemistry, or isotopy). In fact, the relict chondrules in Pontlyfni are not straightforward to identify (Benedix et al, 1998) and were not even identified by Graham et al (1977), while relict chondrules in the other samples are numerous (1.5-5 vol%) and barely altered (Cecchi & Caporali, 2015;Farley et al, 2015;Rubin, 2007;Zeng et al, 2019). As such, it seems that Pontlyfni does not belong to this particular "chondritic achondrite" group and might be the only real winonaite-bearing relict chondrule.…”
Section: Oxygen Isotopic Compositionmentioning
confidence: 91%
“…The modal abundances of NWA 090 and its olivine/opaque ratio (Fig. 3) are evocative of winonaites (Cecchi & Caporali, 2015;Hunt et al, 2017;Zeng et al, 2019). The overlapping of Fs and Fa signatures between NWA 090 and acapulcoites (Fig.…”
Section: Oxygen Isotopic Compositionmentioning
confidence: 93%
See 1 more Smart Citation